Absorption Dips in the Light Curves of GRO J1655–40 and 4U 1630–47 during Outburst - Kuulkers, Erik (1998)
Using the RXTE PCA, we discovered deep dips in the X-ray light curves of the black hole candidates GRO J1655-40 and 4U 1630-47 during outburst. Similar kind of dips for GRO J1655-40 were found in 90 s measurements of the RXTE ASM during the same outburst. The duration of the dips in both sources is of the order of minutes. The occurrences of the dips observed with the RXTE PCA and ASM in GRO J1655-40 are consistent with the optically determined orbital period, and were found between photometric orbital phases 0.72 and 0.86. This constitutes the first evidence for orbital variations in X-rays for GRO J1655-40. The PCA data indicate that an absorbing medium is responsible for these dips. The X-ray spectra during the dips can be best described by a heavily absorbed component and an unabsorbed component. In the case of GRO J1655-40 we are able constrain the extent of the absorbing medium and the central X-ray source.